2006
DOI: 10.1158/1078-0432.ccr-06-0250
|View full text |Cite
|
Sign up to set email alerts
|

c-Met Ectodomain Shedding Rate Correlates with Malignant Potential

Abstract: Purpose: Many proteins are proteolytically released from the cell surface by a process known as ectodomain shedding. Shedding occurs under normal physiologic conditions and can be increased in certain pathologies. Among the many receptors for which ectodomain shedding has been shown is c-Met, the hepatocyte growth factor (HGF) receptor tyrosine kinase. HGF stimulates mitogenesis, motogenesis, and morphogenesis in a variety of cellular targets during development, homeostasis, and tissue regeneration. Inappropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 38 publications
4
82
0
Order By: Relevance
“…The authors concluded that a high MET expression led to an increased potential for tumor metastasis and consequently a poor prognosis (47). These phenomena were similar to those shown in a breast cancer study in which MET shedding correlated with malignancy in cultured cells and tumor burden in tumor xenograft mouse models (48). Conversely, Yang et al demonstrated the beneficial effects of high sMET concentrations in human plasma, showing that the overall median plasma concentration of sMET in patients with gastric cancer was lower than in controls, and sMET levels decreased as the onset of cancer drew nearer (49).…”
Section: Discussionsupporting
confidence: 73%
“…The authors concluded that a high MET expression led to an increased potential for tumor metastasis and consequently a poor prognosis (47). These phenomena were similar to those shown in a breast cancer study in which MET shedding correlated with malignancy in cultured cells and tumor burden in tumor xenograft mouse models (48). Conversely, Yang et al demonstrated the beneficial effects of high sMET concentrations in human plasma, showing that the overall median plasma concentration of sMET in patients with gastric cancer was lower than in controls, and sMET levels decreased as the onset of cancer drew nearer (49).…”
Section: Discussionsupporting
confidence: 73%
“…33,35). Levels of sMET in blood and urine correlated with size and malignant potential of human tumors in xenograft mouse models and in patients (33,(35)(36)(37). Antibody targeting of MET with the bivalent anti-MET antibody DN-30 induced cleavage of the MET ECD, followed by downregulation and proteolytic degradation of the carboxy-terminal fragment (30,31,38,39).…”
Section: Introductionmentioning
confidence: 99%
“…Membranes were washed three times with TBST, incubated with horseradish peroxidase-labeled secondary antibody for 1 h at 25°C, and washed for 3 h with TBS prior to ECL detection (Pierce). Phosphorylated and total Met contents in Triton X-100 cell extracts were determined by an electrochemiluminescent immunoassay read using a SectorImager 2400 (Meso Scale Discovery, Gaithersburg, MD) as described previously (18).…”
Section: Methodsmentioning
confidence: 99%